The Method of Contact Area Assessment between the Femoral Head and Acetabulum in Children that Takes into Account Triradiate Cartilage - Filipchuk, V.V.; Suvorov, V.L.; Melnyk, M.V.; Ziablovskyi, Ye.V. (TERRA ORTHOPAEDICA, 2022)
Relevance. Specific hip joint pathologies in children are characterized by insufficiency of the femoral head (FH) coverage by the acetabulum. This is reflected in the contact area reduction between the FH and acetabulum. In order to correct these acetabular deformities properly, the pediatric orthopedist must know in which direction develops a deficit of contact area between the FH and acetabulum and be able to assess the level of this deficit.Objective: to create an algorithm for the contact area assessment between the FH and acetabulum in children taking into account triradiate cartilage.Materials and Methods. Pelvic CT scans of a 6-year-old male child without hip joint pathologies were selected. A digital model of the pelvis was created using these CT scans. The pelvic model was transferred to a custom-made software, where the contact area between the FH and acetabulum was assessed in an indirect way.Results. The algorithm of the contact area assessment between the FH and acetabulum in children that takes into account triradiate cartilage was developed. Using the abovementioned algorithm, the contact area between the FH and acetabulum from both sides was assessed in a 6-year-old male child.Conclusions. Assessment of the normal contact area between the FH and acetabulum and in various pathological conditions in children will help pediatric orthopedists to understand better different hip joint pathologies and improve preoperative planning.